Fermentation characteristics of elephant grass silages with macaúba cake (Acta Scientiarum. Animal Sciences, 2018)
The elephant grass presents problems during the fermentation of the ensiled material, being necessary use of additives. This study aimed to evaluate the population of yeast and filamentous fungi, enterobacterias, contents of acetic and butyric acids and ethanol production, in elephant grass silages added with different levels of macaúba cake at opening times. This was a 3 x 6 factorial completely randomized experimental design, with three inclusion levels of the macaúba cake (0, 10 and 20%) and six opening times (1, 5, 10, 20, 40 and 60 days after ensiling), with four replications. For all the studied variables, there was a difference in the interaction among levels and times, and an increasing linear behavior only for the contents of acetic acid, for the other variables, the behavior was quadratic. The elephant grass silages produced acetic acid, which in turn inhibited the production of yeast and filamentous fungi. There was a small development of enterobacterias only in the first opening times, and low production of butyric acid and ethanol, which indicated a material with good fermentative characteristics. The macaúba cake contributed to improve the anaerobic fermentation process, but it was not as expressive for the parameters evaluated in this work.